2019
DOI: 10.3389/fnins.2019.00871
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Glycolysis Intermediate Concentrations in the Cerebrospinal Fluid of Alzheimer’s Disease Patients

Abstract: The profile of 122 metabolites in the cerebrospinal fluid (CSF) of patients suffering from Alzheimer’s disease (AD) and controls was studied. Among the 122 metabolites analyzed, 61 could be detected. Statistically significant differences between the AD and control group were only detected for metabolites of the glycolysis. Thus, accurate quantification of 11 glycolytic metabolites was done. We detected a significant reduction of five of them, namely phosphoenolpyruvate, 2-phosphoglycerate, 3-phosphoglycerate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…Specifically, glycolysis has been extensively described for its essential roles in brain development and fast-occurring neuronal activities such as ion transport in neurotransmission. Despite its essential neural functions, glycolysis in the context of AD has not been explored much until recently ( Bergau et al, 2019 ; Butterfield and Halliwell, 2019 ; Theurey et al, 2019 ; Yan et al, 2020 ). Several clinical studies have indicated the involvement of glycolytic dysfunction in the development of AD pathologies ( Vlassenko et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, glycolysis has been extensively described for its essential roles in brain development and fast-occurring neuronal activities such as ion transport in neurotransmission. Despite its essential neural functions, glycolysis in the context of AD has not been explored much until recently ( Bergau et al, 2019 ; Butterfield and Halliwell, 2019 ; Theurey et al, 2019 ; Yan et al, 2020 ). Several clinical studies have indicated the involvement of glycolytic dysfunction in the development of AD pathologies ( Vlassenko et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical study that analyzed 122 metabolites in the CSF of AD and non-AD subjects showed that only intermediates of glycolysis, such as dihydroxyacetone phosphate (DHAP) and phosphoenolpyruvate (PEP), were significantly decreased in AD patients. The reduction of these glycolytic intermediates also exhibited positive correlation with Aβ 1 – 42 and Aβ 1 – 42 /Aβ 1 – 40 ( Bergau et al, 2019 ). A very recent study also reported that astrocytic glycolysis-derived L-serine exhibited a significant decrease in 3xTg-AD mice indicating a reduced glycolytic flux that led to impaired synaptic plasticity and memory ( Le Douce et al, 2020 ).…”
Section: Glycolysis In Admentioning
confidence: 97%
“…In addition, cysteine has been identified as one of the 27 CSF metabolites distinguishable in different types of brain tumors [25]. Glucose levels in CSF are also demonstrated to be decreased in patients with Alzheimer's disease [26]. However, these studies have rarely described control of the postprandial state.…”
Section: Discussionmentioning
confidence: 99%
“…18 and dementia have a left-lateralized rCMRgl decline (Weise et al, 2018). Another study reported a reduction of several glycolysis intermediates in CSF of AD patients compared with controls (Bergau et al, 2019). A recent study with fluorescence lifetime imaging microscopy (FLIM) imaging of primary neurons from transgenic AD mouse showed that these have reduced mitochondrial and cytosolic NAD(P)H, which suggest an impairment in glycolytic flux in these AD neurons (Theurey et al, 2019).…”
Section: Alzheimer's Diseasementioning
confidence: 99%